2020
DOI: 10.1101/2020.07.24.218719
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AD-linked R47H-TREM2mutation induces disease-enhancing proinflammatory microglial states in mice and humans

Abstract: The hemizygous R47H variant of TREM2, a microglia-specific gene in the brain, increases risk for late-onset Alzheimer’s disease (AD). In this study, we identified a subpopulation of microglia with disease-enhancing proinflammatory signatures associated with the R47H mutation in human AD brains and tauopathy mouse brains. Using transcriptomic analysis at the single-nuclei level from AD patients with the R47H or the common variant (CV)-TREM2 with matched sex, pathology and APOE status, we found that the R47H mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 108 publications
(123 reference statements)
0
6
0
Order By: Relevance
“…Very recent studies have shown that tau protein (the other key player in the progression of AD) interacts with the intracellular polyglutamine binding protein 1 (PQBP1), and thereby, it activates pro-inflammatory genes that induce inflammation [60]. In a mouse model of AD, the R47H-TREM2 mutation induced NDD by robustly increasing pro-inflammatory cytokines via hyperactivation of AKT signalization [61].…”
Section: Extracellular Molecular Regulators In Neuroinflammationmentioning
confidence: 99%
“…Very recent studies have shown that tau protein (the other key player in the progression of AD) interacts with the intracellular polyglutamine binding protein 1 (PQBP1), and thereby, it activates pro-inflammatory genes that induce inflammation [60]. In a mouse model of AD, the R47H-TREM2 mutation induced NDD by robustly increasing pro-inflammatory cytokines via hyperactivation of AKT signalization [61].…”
Section: Extracellular Molecular Regulators In Neuroinflammationmentioning
confidence: 99%
“…The most characterised variant of TREM2 (p.R47H) shows defects in ligand binding [6,37,38,97], which impacts the ability of TREM2 to recognise damage, and induce microglial changes, resulting in a dampened response to pathological insults such as Aβ deposition. As TREM2 elicits its functional effect via activation of PLCγ2, it is not surprising that KO of PLCγ2 produces similar phenotypes and, indeed, PLCG2 KO iPSC microglia and macrophages exhibit reduced signalling, phagocytic deficits, and reduction in lipid metabolism, which are also observed in TREM2 KO iPSC lines [34].…”
Section: Trem2 and Plcg2 Load-associated Variants Exhibit Opposing Cementioning
confidence: 99%
“…Studies carried out on IPSCderived microglia-like cells [34] TREM2 p.R47H Impaired myeloid cell response to plaque in vivo and reduced proliferation [37], increased expression of pro-inflammatory cytokines [38], reduced cell adhesion and altered surface levels observed in iPSC-derived macrophages [39] Not clear Shown by [40] to increase apraxia, psychiatric and parkinsonian symptoms when compared to non-carriers, but no differences in clinical phenotype observed by [41] In non-symptomatic carriers, elderly individuals show poor cognitive function [42]). There seems to be too few studies with carriers vs non carriers to draw clear conclusions about the contribution of this variant to disease.…”
Section: Trem2 and Plcg2 Load-associated Variants Exhibit Opposing Cementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a prototypical antiviral immune response is manifested in both pre-clinic models and clinic AD cases. Interestingly, AD patients with rare TREM2 R47H variant, an AD risk factor, have increased presentation of proinflammatory microglia subsets including those enriched with IFN response (Sayed et al, 2020).…”
Section: Antiviral Immune Response In Promoting Ad Pathogenesismentioning
confidence: 99%